2011
DOI: 10.5312/wjo.v2.i4.31
|View full text |Cite
|
Sign up to set email alerts
|

Delayed reconstruction of lateral complex structures of the ankle

Abstract: Lateral ankle instability is one of the most common and well-recognized conditions presenting to foot and ankle surgeons. It may exist as an isolated entity or in conjunction with other concomitant pathology, making it important to appropriately diagnose and identify other conditions that may need to be addressed as part of treatment. These associated conditions may be a source of chronic pain, even when the instability has been appropriately treated, or may lead to failure of treatment by predisposing the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…References [38, 39, 44, 45, 49, 50, 77, 78, 82, 84, 88–90, 107–113, 117, 120–127, 129, 130, 132–134, 136]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…References [38, 39, 44, 45, 49, 50, 77, 78, 82, 84, 88–90, 107–113, 117, 120–127, 129, 130, 132–134, 136]. …”
Section: Resultsmentioning
confidence: 99%
“…References [12, 14, 17, 20–24, 26–29, 31, 32, 34, 44, 48, 51, 73, 75–78, 81, 83, 85, 87, 89, 93–96, 99, 100, 103, 109–111, 114, 117, 119–121, 123, 131, 134–137]. …”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also shown a significant incidence of associated injuries identified with arthroscopy, thus supporting its role as an adjuvant to surgical repair [33][34][35] Those patients that go on to surgical repair for chronic instability with anatomic techniques, such as a modified Brostrom, tend to have satisfaction rates greater than 85%. Other techniques, which use either tissue from another location in the patient's ankle or tissue from a cadaver, tend to have lower satisfaction rates when compared to anatomic repair techniques 33,[36][37][38] . No strong evidence exists to suggest that nonanatomic reconstruction leads to better outcomes.…”
Section: Outcomes/results Of Treatment/prognosismentioning
confidence: 99%
“…Pacientes com instabilidade do tornozelo habitualmente apresentam-se para o tratamento após sofrer uma entorse severa de tornozelo que progrediu para recorrente (9,10) . O diagnóstico é baseado nos achados clínicos e é realizado quando há elevada frouxidão nas manobras de gaveta anterior e inversão quando comparadas ao tornozelo contralateral.…”
Section: Introductionunclassified
“…O tratamento pode ser cirúrgico ou conservador com analgesia associada à fisioterapia para propriocepção e reforço de fibulares, tornozeleiras e adequações nas modalidades esportivas. Dentre as diversas técnicas cirúrgicas existem, por exemplo, o reparo direto ligamentar chamado de Brostrom, a reconstrução não anatômica chamada de Chrisman-Snook e a reconstrução anatômica com enxerto tendíneo que é o foco deste estudo (10)(11)(12) . O objetivo deste trabalho é avaliar os resultados clínicos e radiográficos dos pacientes operados por instabilidade la teral crônica do tornozelo com a técnica de reconstrução anatômica com autoenxerto de tendões flexores do joelho, através da melhora dos marcadores radiográficos de estresse em varo e gaveta anterior, bem como do escore AOFAS, comparando os resultados encontrados na literatura mundial (13,14) .…”
Section: Introductionunclassified